Positive electrode active material, method of preparing same, positive electrode including same, and rechargeable lithium battery including positive electrode

By using layered lithium nickel-manganese composite oxides and forming Al and Mn coatings on their surfaces, the problems of shortage of cobalt supply in the positive electrode active substances of existing lithium batteries and gas generation under high temperature and high pressure conditions are solved, and the effects of high capacity and long cycle life are achieved.

CN119542370APending Publication Date: 2025-02-28SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411173705.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-24
Filing Date
2024-08-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The positive electrode active substances of existing rechargeable lithium batteries contain rare metal cobalt, which leads to shortage of supply and increased costs, and is easy to generate gas under high voltage and high temperature conditions, reducing cycle life.

Method used

The layered lithium nickel-manganese composite oxide is used as the positive electrode active material, and a coating of Al and Mn is formed on its surface, and the material is prepared by the first heat treatment and the second heat treatment.

Benefits of technology

High capacity, long cycle life and improved high voltage and high temperature characteristics are achieved, reducing the amount of gas generated under these conditions and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542370A_ABST
    Figure CN119542370A_ABST
Patent Text Reader

Abstract

The present disclosure discloses a positive electrode active material, a method of preparing the same, a positive electrode including the same, and a rechargeable lithium battery including the positive electrode. The positive electrode active material includes a core particle including a layered lithium nickel manganese-based composite oxide, a first coating layer provided on a surface of the core particle and containing Al, and a second coating layer provided on the first coating layer and containing Mn.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material, a preparation method thereof, a positive electrode including the same, and a rechargeable lithium battery including the positive electrode. Background Art

[0002] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) and / or electric vehicles have used rechargeable lithium batteries with relatively high energy density and easy portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with relatively high energy density as driving power sources for hybrid vehicles and / or electric vehicles, or as power storage power sources for home power storage units and / or power walls.

[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries suitable for these applications. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, although the demand for rechargeable lithium batteries with large size, relatively high capacity or relatively high energy density has increased recently, it is expected that the supply of positive electrode active materials containing rare metal cobalt is in short supply (severe shortage). For example, because cobalt is expensive and lacks residual reserves (for example, availability decreases), it is necessary to develop a positive electrode active material that excludes cobalt (for example, does not include cobalt or is cobalt-free) or uses cobalt in a reduced amount. Summary of the invention

[0004] Aspects according to some embodiments relate to: a positive electrode active material comprising a layered lithium nickel manganese-based composite oxide, ensuring economic feasibility, high capacity and long cycle life characteristics, and exhibiting improved high voltage characteristics and high temperature characteristics; a method for preparing the positive electrode active material; a positive electrode; and a rechargeable lithium battery comprising the positive electrode active material.

[0005] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments of the disclosure.

[0006] In one or more embodiments, the positive electrode active material includes: a core particle including a layered lithium nickel manganese composite oxide (for example, (for example, each) a core particle including a layered lithium nickel manganese composite oxide), a first coating layer on the surface of the core particle and containing Al, and a second coating layer on the first coating layer and containing Mn.

[0007] In one or more embodiments, the method for preparing the aforementioned positive electrode active material includes: mixing a nickel manganese composite hydroxide and a lithium raw material, and performing a first heat treatment to obtain a layered lithium nickel manganese composite oxide; mixing an Al raw material with an aqueous solvent, adding a layered lithium nickel manganese composite oxide and mixing to prepare a first mixture, and mixing a Mn raw material and the first mixture to prepare a second mixture; and drying the second mixture and performing a second heat treatment.

[0008] In one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.

[0009] In one or more embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte.

[0010] The positive electrode active material according to one or more embodiments can maximize or increase capacity while minimizing or reducing production costs to ensure long cycle life characteristics and improve high voltage characteristics and high temperature characteristics. When the positive electrode active material is applied to a rechargeable lithium battery, a high initial charge / discharge capacity and efficiency can be achieved under high voltage operating conditions, a long cycle life characteristic can be achieved, and the amount of gas generated due to high voltage and high temperature operation can be effectively suppressed or reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The accompanying drawings are included to provide a further understanding of the present disclosure and are incorporated in and constitute a part of this specification. The accompanying drawings illustrate embodiments of the present disclosure and together with the description serve to explain the principles of the present disclosure. In the accompanying drawings,

[0012] Figure 1 is a schematic illustration of a cylindrical battery according to some embodiments.

[0013] Figure 2 is a schematic illustration of a prismatic battery according to some embodiments.

[0014] Figure 3 is a schematic illustration of a pouch-type or similar battery according to some embodiments.

[0015] Figure 4 is a schematic illustration of a pouch-type or similar battery according to some embodiments.

[0016] Figure 5 FIG. 1 is a SEM-EDS image of a cross section of the positive electrode active material of Example 1, in which Mn is highlighted.

[0017] Figure 6This is a SEM-EDS image of a cross section of the positive electrode active material of Example 1, in which Al is highlighted.

[0018] Figure 7 This is a HR-STEM image of a cross section of the positive electrode active material of Example 1.

[0019] <Reference Numbers>

[0020] 100: Rechargeable lithium battery 10: Positive electrode

[0021] 11: Positive electrode lead lug 12: Positive electrode terminal

[0022] 20: Negative electrode 21: Negative electrode lead lug

[0023] 22: Negative electrode terminal 30: Separator

[0024] 40: electrode assembly 50: shell

[0025] 60: Sealing member 70: Electrode terminal piece

[0026] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION

[0027] Hereinafter, the embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and should not be construed as limited to the example embodiments set forth herein.

[0028] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.

[0029] As used herein, the term "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of components.

[0030] In this document, it should be understood that terms such as "comprises", "includes" or "have" are intended to indicate the presence of implemented features, quantities, (e.g., actions or tasks) steps, elements or combinations thereof, but it does not exclude the possibility of the presence or addition of one or more other features, quantities, (e.g., actions or tasks) steps, elements or (e.g., any appropriate) combinations thereof.

[0031] In the accompanying drawings, the size (e.g., thickness) of layers, films, panels, regions, etc. is exaggerated for clarity, and the same reference numerals represent the same elements throughout, and their repeated description may not be provided in the specification. It will be understood that if (e.g., when) an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate), or there may also be intervening elements. In contrast, if (e.g., when) an element is referred to as being "directly on" another element "(such as a layer, film, region, or substrate), there are no intervening elements (when).

[0032] In addition, the term "layer" as used herein, if (for example, when) viewed from a plan view, includes not only a shape formed on the entire surface but also a shape formed on a partial surface.

[0033] In addition, the average particle size can be measured by an appropriate method (e.g., a method known to those skilled in the art) (e.g., by a particle size analyzer, or by a transmission electron microscopy image or a scanning electron microscopy image). In one or more embodiments, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. As used herein, if (for example, when) no other definition is provided, the average particle diameter (D 50 ) refers to the diameter of particles accounting for 50% by volume of the cumulative volume in a particle size distribution obtained by randomly measuring the sizes (diameters or major axis lengths) of about 20 particles in a scanning electron microscope image.

[0034] In this document, the term "or" is not to be interpreted as an exclusive meaning. For example, "A or B" means A, B, A+B, etc.

[0035] As used herein, the term "metal" refers to common metals, transition metals, and metalloids (semimetals).

[0036] Positive electrode active material

[0037] In one or more embodiments, the positive electrode active material includes: a core particle (e.g., one or more core particles) including a layered lithium nickel manganese composite oxide (hereinafter, referred to as "lithium nickel manganese composite oxide"), a first coating layer arranged on the surface of the core particle and containing Al, and a second coating layer arranged on the first coating layer and containing Mn.

[0038] Since the price of rare metal cobalt has risen sharply recently, it is necessary to develop a positive electrode active material that excludes (does not include) cobalt or has a reduced cobalt content (e.g., amount). Among them, positive electrode active materials with olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese iron phosphate (LMFP), etc.) or positive electrode active materials with spinel crystal structure (such as lithium manganese oxide (LMO), etc.) are limited in achieving high capacity due to the small available lithium capacity in their structure. Due to the high available lithium capacity in the structure, the layered lithium nickel manganese positive electrode active material has excellent or appropriate capacity and efficiency characteristics, making it suitable as a material for high-capacity batteries. However, as cobalt, which plays a key role in the layered structure, is removed, the structural stability is reduced, the resistance is increased, and it becomes difficult to ensure long cycle life characteristics. In addition, the elimination of cobalt leads to the problem that the side reaction between the positive electrode active material and the electrolyte is accelerated under high voltage and high temperature conditions, thereby increasing the amount of generated gas and deteriorating the cycle life characteristics.

[0039] In some embodiments, a first coating layer and a second coating layer are introduced on the core particles of the layered lithium nickel manganese-based composite oxide to provide a positive electrode active material that can maximize or increase capacity and efficiency and achieve long cycle life characteristics by reducing gas generation even under high voltage or high temperature conditions.

[0040] Nuclear particles

[0041] The core particles include lithium nickel manganese composite oxides. Based on 100mol% of the total metals other than lithium in the lithium nickel manganese composite oxide, the nickel content (e.g., amount) may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced, high capacity can be achieved and structural stability can be increased.

[0042] For example, based on 100 mol% of the total metals other than lithium in the lithium nickel manganese composite oxide, the manganese content (e.g., amount) may be greater than or equal to about 10 mol%, such as about 10 mol% to about 40 mol%, about 15 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%. If the manganese content (e.g., amount) satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.

[0043] The lithium nickel manganese composite oxide may be, for example, a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. When the lithium nickel manganese composite oxide includes aluminum, it is advantageous or suitable for maintaining a stable layered structure even if the element cobalt is excluded from the structure. The aluminum content (e.g., amount) based on 100 mol% of the lithium nickel manganese aluminum composite oxide (e.g., the total metal other than lithium in the lithium nickel manganese aluminum composite oxide) may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 2.5 mol%. If the aluminum content (e.g., amount) satisfies the above range, even if cobalt is excluded, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.

[0044] According to one or more embodiments, the concentration of aluminum in the core particle can be substantially uniform. In some embodiments, there is no concentration gradient of aluminum from the center to the surface in the core particle, or the aluminum concentration of the inner part of the core particle is neither higher than nor lower than the aluminum concentration of the outer part, and the aluminum is uniformly distributed in the core particle. It can be a structure obtained by using an aluminum raw material (hereinafter, also referred to as "Al raw material") during precursor production, and not additionally doping aluminum during the synthesis of the core particle, thereby using nickel-manganese-aluminum hydroxide as a precursor to synthesize lithium-nickel-manganese-aluminum composite oxides. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated (e.g., agglomerated), and the aluminum content (e.g., amount) inside the primary particle may be the same (or substantially the same) or similar, regardless of the position of the primary particle. For example, if a primary particle is selected at a random position in the cross section of the secondary particle, and the aluminum content (e.g., amount) is measured inside the primary particle rather than at its interface (e.g., with another primary particle), the aluminum content (e.g., amount) can be (e.g., appropriately) the same / similar / uniform regardless of the position of the primary particle (i.e., whether the primary particle is near the center of the secondary particle or near its surface). In this structure, even if cobalt is not present or present in a very small amount, a stable layered structure can be maintained, and aluminum byproducts or aluminum aggregates are not generated, thereby simultaneously improving the capacity, efficiency, and cycle life characteristics of the positive electrode active material.

[0045] In some embodiments, the lithium nickel manganese-based composite oxide may be represented by Chemical Formula 1.

[0046] [Chemical formula 1]

[0047] Li a1 Ni x1 Mn y1 Alz1 M 1 w1 O 2-b1 X b1

[0048] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.8, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.4, 0 ≤ z1 ≤ 0.03, 0 ≤ w1 ≤ 0.3, 0.9 ≤ x1 + y1 + z1 + w1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.

[0049] In some embodiments, in Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. In some embodiments, Chemical Formula 1 may contain aluminum, in which case 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29, and may satisfy, for example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29.

[0050] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09.

[0051] The lithium nickel manganese composite oxide may be a cobalt-free compound that does not include cobalt or includes a very small amount of cobalt. For example, based on the total metals other than lithium in 100 mol% of the lithium nickel manganese composite oxide, the cobalt content (e.g., amount) of the lithium nickel manganese composite oxide may be from about 0 mol% to about 0.01 mol%.

[0052] The core particle may be in the form of a secondary particle made by aggregating a plurality of primary particles. The secondary particle may be spherical, ellipsoidal, polyhedral or irregular in shape, and the primary particle may be spherical, ellipsoidal, plate-like or (eg, any appropriate) combination thereof.

[0053] If (for example, when) the battery is operated under high voltage and / or high temperature conditions, the core particles are susceptible to chemical attack by components in the electrolyte, and side reactions with the electrolyte may occur. Accordingly, there may be a problem of reducing the battery cycle life and safety due to the generation of a large amount of gas. These problems can be solved by introducing a coating according to one or more embodiments that will be described in more detail later.

[0054] First coating

[0055] Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the Al content (e.g., amount) in the first coating layer may be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%. The Al content (e.g., amount) refers only to the aluminum content (e.g., amount) contained in the first coating layer, which is separated from the aluminum contained in the core particles (excluding the aluminum included in the core particles). The aluminum content (e.g., amount) in the first coating layer can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If (e.g., when) the aluminum content (e.g., amount) in the first coating layer satisfies these ranges, the coating layer may have a substantially uniform and thin thickness, which does not increase the resistance of the positive electrode active material, while effectively inhibiting or reducing side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, if the aluminum content (e.g., amount) of the first coating layer is too much (e.g., greater than about 2 mol%), a substantially uniform coating layer may not be formed or resistance may increase, which may reduce charge / discharge efficiency and cycle life characteristics, and if the aluminum content (e.g., amount) of the first coating layer is too little (e.g., less than about 0.1 mol%), a coating layer of suitable or appropriate thickness may not be formed and the effect of suppressing or reducing side reactions with the electrolyte may be reduced.

[0056] The first coating may be in the form of a film that continuously surrounds the surface of the core particle, for example, it may be in the form of a shell that surrounds the surface of the entire core particle. This is different from a structure in which only a portion of the surface of the core particle is partially coated. According to one or more embodiments, the first coating may be formed to cover the entire surface of the core particle, and may be formed to be thin (e.g., very thin) and substantially uniform in thickness, so that the positive electrode active material does not increase resistance or reduce capacity, improves structural stability, effectively inhibits side reactions with the electrolyte, reduces the amount of gas generated under high voltage and high temperature conditions, and achieves long cycle life characteristics.

[0057] The thickness of the coating may be about 5 nanometers (nm) to about 40 nm, for example, about 5 nm to about 30 nm or about 5 nm to about 20 nm. When the coating meets these thickness ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, scanning electron microscopy (SEM), transmission electron microscopy (TEM), time-of-flight-secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS) or energy dispersive X-ray spectroscopy (EDS), and the thickness range of the coating can be measured by TEM-EDS line profile.

[0058] The first coating may be thicker than the second coating.

[0059] The first coating layer may be thin and substantially uniform in thickness, at a level of a few nanometers to tens of nanometers. For example, the deviation of the coating thickness within a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness within a positive electrode active material particle. For example, the deviation of the coating thickness can be calculated by measuring the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle to calculate the arithmetic mean, and then the absolute value of the difference between a measurement data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100. The fact that the deviation or standard deviation of the first coating thickness meets the above range indicates that a coating layer of substantially uniform thickness is formed (e.g., well formed) in the form of a film on the surface of the core particle of the positive electrode active material. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the increase in impedance or the decrease in capacity due to the coating can be minimized or reduced.

[0060] The first coating layer may include, for example, aluminum oxide, lithium aluminum oxide, or a combination thereof (eg, any suitable combination). The first coating layer may have a layered structure. For example, the compound included in the first coating layer may have a layered structure.

[0061] In one or more embodiments, the first coating may further contain nickel, manganese, or (eg, any suitable) combination thereof in addition to aluminum.

[0062] Second coating

[0063] Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the Mn content (e.g., amount) in the second coating layer may be about 0.01 mol% to about 1 mol%, such as about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.05 mol% to about 0.5 mol%, or about 0.1 mol% to about 0.4 mol%. The Mn content (e.g., amount) in the second coating layer may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the Mn content (e.g., amount) in the second coating layer satisfies these ranges, the coating layer may have a substantially uniform and thin thickness, which does not increase the resistance of the positive electrode active material, and may effectively inhibit or reduce side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, if the Mn content (e.g., amount) of the second coating layer is too much (e.g., greater than about 1 mol%), a substantially uniform coating layer may not be formed or resistance may increase, which may reduce charge efficiency / discharge efficiency and cycle life characteristics, and if the Mn content (e.g., amount) of the second coating layer is too little (e.g., less than about 0.01 mol%), a coating layer of a suitable or appropriate thickness may not be formed, and the effect of suppressing or reducing side reactions with the electrolyte may be reduced.

[0064] The second coating layer may be in the form of a film or shell that continuously surrounds (e.g., completely surrounds) the surface of the first coating layer. According to one or more embodiments, because the coating layer is formed to completely surround the outermost surface of the positive electrode active material, but still has a very thin and substantially uniform thickness, the positive electrode active material may neither show an increase in resistance nor deteriorate capacity, but may improve structural stability, effectively inhibit or reduce side reactions with the electrolyte, reduce gas generation, and achieve long-term cycle life characteristics.

[0065] The thickness of the second coating layer may be less than or equal to about 10 nm, for example, about 0.1 nm to about 10 nm, about 0.5 nm to about 9 nm, about 1 nm to about 7 nm, or about 1 nm to about 5 nm. If the second coating layer meets these ranges of thickness, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating layer, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating layer can be measured by, for example, SEM, TEM, TOF-SIMS, XPS or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profile.

[0066] The second coating according to one or more embodiments may be thin and substantially uniform in thickness, at the level of a few nanometers to tens of nanometers. For example, the variation in the thickness of the second coating within a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness within a positive electrode active material particle. For example, the deviation of the coating thickness can be calculated by measuring the thickness of about 10 points in an electron microscope image of a cross section of a single positive electrode active material particle to calculate the arithmetic mean, and then the absolute value of the difference between a measurement data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100. The fact that the deviation or standard deviation of the second coating thickness meets the above range indicates that a coating of substantially uniform thickness is formed (e.g., well formed) in the form of a film on the surface of the core particle of the positive electrode active material. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the increase in resistance or the decrease in capacity due to the coating can be minimized or reduced.

[0067] In some embodiments, in addition to Mn, the second coating may further include Al. The second coating may include, for example, manganese oxide, lithium manganese oxide, aluminum manganese oxide, lithium aluminum manganese oxide, or (e.g., any suitable) combination thereof. The second coating may have a layered structure. In some embodiments, the second coating may further have a spinel structure.

[0068] In one or more embodiments, the first coating layer may be thicker than the second coating layer. For example, the ratio of the thickness of the second coating layer to the thickness of the first coating layer may be less than or equal to about 0.5, such as less than or equal to about 0.4 or less than or equal to about 0.3. When the thickness of the first coating layer and the thickness of the second coating layer satisfy this relationship, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating layer; and the high voltage characteristics and high temperature characteristics can be improved by effectively suppressing or reducing side reactions with the electrolyte.

[0069] The Al content (e.g., amount) of the first coating layer may be greater than the Mn content (e.g., amount) of the second coating layer. In this article, the content (e.g., amount) may refer to the molar content (e.g., amount) or the molar content (e.g., amount) of the total metal other than lithium relative to 100 mol% in the positive electrode active material. For example, the ratio of the Mn content (e.g., amount) of the second coating layer to the Al content (e.g., amount) of the first coating layer may be at most 0.5, may be less than 0.5, for example, less than or equal to about 0.4 or less than or equal to about 0.3. When the Al content (e.g., amount) of the first coating layer and the Mn (e.g., amount) content of the second coating layer satisfy this relationship, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating layer; and the high voltage characteristics and high temperature characteristics can be improved by effectively suppressing or reducing side reactions with the electrolyte.

[0070] Grain boundary coating part

[0071] In one or more embodiments, during the first coating formation process, aluminum may diffuse into the core particles. Accordingly, the positive electrode active material according to one or more embodiments may further include a grain boundary coating portion, which includes aluminum and is arranged on the surface of the primary particles in the inner portion of the secondary particles. In this article, the secondary particle refers to the core particle, and the inner portion of the secondary particle may refer to the entire inner portion except the surface of the secondary particle, or the inner portion may be a zone of about 60% of the radius of the secondary particle (i.e., the distance from the surface of the secondary particle to the center of the secondary particle) from the center of the secondary particle to the surface of the secondary particle. The grain boundary coating is different from the coating on the surface of the core particle, and refers to the coating portion formed on the surface of the primary particle inside the core particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming an aluminum grain boundary coating portion, the positive electrode active material can become more structurally stable and its cycle life characteristics can be improved.

[0072] The aluminum content (eg, amount) in the grain boundary coating portion is not particularly limited, and, for example, the aluminum content (eg, amount) in the grain boundary coating portion may be smaller than the aluminum content (eg, amount) in the first coating layer.

[0073] In some embodiments, in addition to aluminum, the grain boundary coating portion may further include nickel, magnesium, yttrium, or (eg, any suitable) combination thereof.

[0074] The average particle size (D 50) is not particularly limited, but may be, for example, about 1 micron or micrometer (μm) to about 25 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 11 μm to about 18 μm, or about 12 μm to about 15 μm. As used herein, if (for example, when) no other definition is provided, the average particle size (D) of the secondary particles is 50 ) refers to the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image of a positive electrode active material. If the average particle size of the secondary particles of the positive electrode active material satisfies the above range, high capacity and long cycle life can be achieved, and it can be suitable for or conducive to forming a coating according to one or more embodiments.

[0075] The cobalt content (e.g., amount) in the positive electrode active material according to one or more embodiments may be, for example, less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, for example, from about 0 mol% to about 0.01 mol%, based on 100 mol% of the total metals other than lithium in the positive electrode active material. The positive electrode active material according to one or more embodiments may be, for example, a cobalt-free positive electrode active material.

[0076] In one or more embodiments, the positive electrode active material may not include (may exclude) sodium. In the related art, sodium ions can be used in the preparation process of the positive electrode active material, but according to the preparation method described in more detail later, a core particle having a stable structure and a coating layer of substantially uniform thickness can be formed without using sodium ions.

[0077] Method for preparing positive electrode active material

[0078] In one or more embodiments, the method for preparing a positive electrode active material includes: mixing a nickel-manganese composite hydroxide and a lithium raw material, and performing a first heat treatment to obtain a lithium-nickel-manganese composite oxide; adding an Al raw material to an aqueous solvent and mixing, adding a lithium-nickel-manganese composite oxide, and then mixing to prepare a first mixture, and adding a Mn raw material to the first mixture, and then mixing to prepare a second mixture; and drying the second mixture and performing a second heat treatment. The aforementioned positive electrode active material can be prepared by the aforementioned method.

[0079] The layered nickel-manganese composite hydroxide (i.e., nickel-manganese composite hydroxide) as a core particle precursor may be in the form of secondary particles in which a plurality of primary particles are aggregated (e.g., agglomerated), and may not contain cobalt or may contain a very small amount of cobalt. For example, the nickel-manganese composite hydroxide may be a cobalt-free nickel-manganese composite hydroxide. The nickel-manganese composite hydroxide may be prepared by an appropriate (e.g., general) coprecipitation method.

[0080] Based on 100mol% of the total metal in the nickel-manganese composite hydroxide, the nickel content (e.g., amount) in the nickel-manganese composite hydroxide may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If (e.g., when) the nickel content (e.g., amount) satisfies the above range (when), even if the cobalt content (e.g., amount) is reduced, high capacity can be achieved and structural stability can be increased.

[0081] The manganese content (e.g., amount) in the layered nickel-manganese-based composite hydroxide may be greater than or equal to about 10 mol%, for example, about 10 mol% to about 40 mol%, about 15 mol% to about 39 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%, based on 100 mol% of total metals in the layered nickel-manganese-based composite hydroxide.

[0082] In one or more embodiments, if (for example, when) the nickel-manganese composite hydroxide further contains aluminum (that is, the nickel-manganese composite hydroxide is a nickel-manganese-aluminum composite hydroxide), then the aluminum content (for example, amount) based on 100 mol% of the total metal in the nickel-manganese composite hydroxide may be greater than 0 mol% and less than or equal to 3 mol%, for example, greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, 0 mol% to 3 mol%, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If the manganese and aluminum contents of the nickel-manganese composite hydroxide meet the above ranges, high capacity can be achieved, the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.

[0083] In the method for preparing a positive electrode active material according to some embodiments, when preparing the core particles, aluminum is not additionally doped, but an aluminum raw material can be used to prepare a precursor, so that a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly (e.g., substantially uniformly) dispersed in the structure can be used as a precursor. When such a precursor is used, the positive electrode active material can stably maintain a layered structure without cobalt despite repeated charging and discharging, and aluminum byproducts or aluminum aggregates may not be formed, thereby improving the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material.

[0084] In the layered nickel-manganese composite hydroxide, the cobalt content (e.g., amount) may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, based on 100 mol% of the total metal in the layered nickel-manganese composite hydroxide, for example, 0 mol% to 0.01 mol%. Such a nickel-manganese composite hydroxide may be economical because it avoids the increase in unit cost caused by cobalt, maximizes or increases capacity, and improves structural stability.

[0085] In some embodiments, the layered nickel-manganese-based composite hydroxide may be represented by Chemical Formula 2.

[0086] [Chemical formula 2]

[0087] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2

[0088] In Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr.

[0089] In some embodiments, in Chemical Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.

[0090] The layered nickel-manganese composite hydroxide is in the form of particles, and the average particle size (D 50 ) may be about 1 μm to about 25 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 11 μm to about 18 μm, or about 12 μm to about 15 μm.

[0091] The layered nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8, for example, about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2. The first heat treatment can be carried out in an oxygen atmosphere, for example, in a temperature range of about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By heat treatment, a lithium nickel-manganese composite oxide can be obtained. The obtained lithium nickel-manganese composite oxide is substantially the same as the lithium nickel-manganese composite oxide described for the core particles in the positive electrode active material section.

[0092] The lithium nickel manganese composite oxide has a significantly different residual lithium content (e.g., amount) and different surface characteristics from oxides having other compositions (e.g., nickel oxides of the related art, such as lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, etc.), and the coating method of the related art may not be able to successfully form a good or appropriate coating in the form of a substantially uniform film thereon. In one or more embodiments, such a method (by uniformly (e.g., substantially uniformly) forming a coating with a very thin thickness on the surface of a layered lithium nickel manganese composite oxide having a very small amount of cobalt and a nickel content (e.g., amount) greater than or equal to about 60 mol%) is applied to improve high voltage characteristics.

[0093] In one or more embodiments, the Al raw material is added to an aqueous solvent and mixed, and then a layered lithium nickel manganese composite oxide is added and mixed to provide (e.g., introduce) a first coating on the surface of the layered lithium nickel manganese composite oxide particles (core particles). Subsequently, the Mn raw material is added to the mixed solution and mixed to provide (e.g., introduce) a second coating. After removing the solvent from the mixed solution and drying, a second heat treatment is performed to obtain a positive electrode active material in which a first coating containing Al and a second coating containing Mn are sequentially formed on the surface of the core particles. This can be referred to as a continuous wet coating method.

[0094] The aqueous solvent may include distilled water, an alcohol solvent, or a combination thereof (e.g., any suitable combination). The Al raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof (e.g., any suitable combination). For example, the Al raw material may include aluminum sulfate, and in this case, it is suitable or beneficial to form a first coating having a substantially uniform thickness on the surface of the lithium nickel manganese composite oxide particles.

[0095] Based on 100 mol% of the total metals other than lithium in the positive electrode active material, the Al content (e.g., amount) in the aluminum raw material can be designed to be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%. If the Al content (e.g., amount) in the first coating layer is designed to have these ranges, the first coating layer can be formed to have a thin and substantially uniform thickness of several nanometers to tens of nanometers, which can reduce the amount of gas generated in a rechargeable lithium battery under high voltage or high temperature operating conditions, and improve high capacity and long cycle life characteristics.

[0096] The solution obtained by mixing the aluminum raw material in an aqueous solvent may have a pH of about 1.5 to about 3.5, for example, about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2. Adding (e.g., dropping) and mixing the lithium nickel manganese composite oxide to the aqueous solvent mixed with the aluminum raw material may be performed for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5, for example, about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0. When these conditions are met, it is suitable for or conducive to forming a first coating having a substantially uniform thickness.

[0097] The Mn raw material may include, for example, manganese nitrate, manganese sulfate, manganese carbonate, manganese hydroxide, or (for example, any appropriate) combination thereof. Based on 100 mol% of the total metal other than lithium in the positive electrode active material, the Mn content (for example, amount) of the Mn raw material may be designed to be about 0.01 mol% to about 1 mol%, for example, about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.05 mol% to about 0.5 mol%, or about 0.1 mol% to about 0.4 mol%. If the Mn content (for example, amount) in the second coating is designed to have these ranges, the second coating may be formed to have a thin and substantially uniform thickness of several nanometers to tens of nanometers, which may improve the performance of the rechargeable lithium battery under high voltage or high temperature operating conditions, as well as high capacity and long cycle life characteristics.

[0098] The addition and mixing of the Mn raw material may be performed for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 10 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5, such as about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0. If these conditions are met, it is suitable for or conducive to forming a second coating layer having a substantially uniform thickness.

[0099] Removal of the solvent and drying of the residue may be performed, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C.

[0100] The second heat treatment may be performed, for example, in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 hours to about 10 hours. In addition, the second heat treatment temperature may be lower than the first heat treatment temperature, and the second heat treatment time may be the same as the first heat treatment time or shorter than the first heat treatment time. A desired or appropriate coating may be obtained by performing a second heat treatment under these conditions.

[0101] Positive electrode

[0102] In one or more embodiments, the electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material described above. In addition to the positive electrode active material described above, the positive electrode active material layer may further include other types (kinds) of positive electrode active materials. In addition, the positive electrode active material layer may optionally further include a binder, a conductive material (e.g., an electrical conductor) or a combination thereof (e.g., any appropriate).

[0103] According to one or more embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . In addition, the density of the positive electrode active material layer in the final pressed positive electrode may be about 3.3 g / cc to about 3.7 g / cc, for example, about 3.3 g / cc to about 3.6 g / cc or about 3.4 g / cc to about 3.58 g / cc. When applying the positive electrode active material according to one or more embodiments, it is desirable or advantageous to implement such a loading level and density of the positive electrode active material layer, and the positive electrode in which the loading level and density of the positive electrode active material layer meet the above range is suitable for implementing a high-capacity, high-energy-density rechargeable lithium battery.

[0104] Binder

[0105] The binder improves the bonding properties of the positive electrode active material particles to each other and to the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin or nylon, but the present disclosure is not limited thereto.

[0106] Conductive Materials

[0107] A conductive material (e.g., an electrical conductor) is included to provide electrode conductivity, and any suitable conductive material may be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and / or (e.g., any suitable) mixtures thereof.

[0108] Each content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt % based on 100 wt % of the positive electrode active material layer.

[0109] The positive electrode current collector may include an Al foil, but the present disclosure is not limited thereto.

[0110] Rechargeable lithium battery

[0111] According to some embodiments, a rechargeable lithium battery includes: the aforementioned positive electrode, negative electrode and electrolyte. As an example, a rechargeable lithium battery may include a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte.

[0112] Rechargeable lithium batteries may be classified into cylindrical batteries, prismatic batteries, pouch batteries, coin batteries, etc., depending on the shape. Figure 1 to Figure 4 is a schematic diagram showing a rechargeable lithium battery according to one or more embodiments, wherein Figure 1 A cylindrical (eg, circular) battery is shown, Figure 2 A rectangular parallelepiped (eg, cube) battery is shown, and Figure 3-4 Each shows a pouch-shaped battery. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes: an electrode assembly 40 having a separator 30 disposed between a positive electrode 10 and a negative electrode 20, and a case 50 accommodating the electrode assembly 40. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution. Figure 1As shown in FIG, the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 2 In the embodiment, the lithium rechargeable battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3-4 As shown in FIG. 1 , the rechargeable lithium battery 100 includes electrode tabs 70 , ie, a positive electrode tab 71 and a negative electrode tab 72 , which serve as an electrical path for introducing current generated in the electrode assembly 40 to the outside.

[0113] The rechargeable lithium battery according to some embodiments may be rechargeable at a high voltage, or may be suitable for being driven at a high voltage. For example, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to one or more embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even (for example, when) charging at a high voltage, and can achieve high capacity and long cycle life characteristics.

[0114] Negative electrode

[0115] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and may further include a negative electrode active material, a binder, a conductive material (eg, an electrical conductor), or (eg, any appropriate) combination thereof.

[0116] Negative electrode active material

[0117] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.

[0118] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or (for example, any appropriate) combination thereof as a carbon-based negative electrode active material. Crystalline carbon may be natural graphite or artificial graphite in an amorphous or flaky, flake-like, spherical or fibrous (for example, in the form of fibers). Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.

[0119] Lithium metal alloys include alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0120] The material capable of being doped / undoped with lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x(0 < x ≤ 2), Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and their (e.g., any suitable) combinations, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or their (e.g., any suitable) combinations) or their combinations. The Sn-based negative electrode active material can be Sn, SnO x (0 < x < 2, e.g., SnO2), Sn alloy, or their (e.g., any suitable) combinations.

[0121] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles (e.g., secondary particles) can be, for example, about 0.5 μm to about 20 μm. According to one or more embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it can include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the silicon primary particles. For example, the silicon primary particles can be coated with amorphous carbon. The secondary particles can be dispersed in the amorphous carbon matrix.

[0122] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include: a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or their (e.g., any suitable) combinations. The amorphous carbon can include soft carbon, hard carbon, mesophase pitch carbonization products, and calcined coke.

[0123] If the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon can be about 10 wt% to about 50 wt% and the content (e.g., amount) of amorphous carbon can be about 50 wt% to about 90 wt%. In one or more embodiments, if the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon can be about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon can be about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon can be about 20 wt% to about 40 wt%.

[0124] In some embodiments, the thickness of the amorphous carbon coating can be about 5 nm to about 100 nm. The average particle size (D 50 ) of the silicon particles (primary particles) can be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles can exist as silicon alone, in the form of a silicon alloy, or in the oxidized form of silicon. The oxidized form of silicon can be represented by SiO x (0 < x ≤ 2). At this time, the atomic content (e.g., amount) ratio of Si:O indicating the degree of oxidation can be about 99:1 to about 33:67. As used herein, if (e.g., when) no other definition is provided otherwise, the average particle size (D 50 ) indicates the diameter of the particles with a cumulative volume of about 50% by volume in the particle size distribution.

[0125] The Si-based negative electrode active material or the Sn-based negative electrode active material can be mixed with the carbon-based negative electrode active material. If (e.g., when) the Si-based negative electrode active material or the Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material and used, the mixing ratio can be a weight ratio of about 1:99 to about 90:10.

[0126] Binder

[0127] The binder is used to bond the negative electrode active material particles to each other (e.g., bond well), and is also used to bond the negative electrode active material to the negative electrode current collector. The binder can be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0128] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof (e.g., any suitable combination).

[0129] The aqueous binder can include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, poly(ethylene oxide), polyvinylpyrrolidone, poly(epichlorohydrin), polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof (e.g., any suitable combination).

[0130] If (e.g., when) the aqueous binder is used as the binder in the negative electrode active material layer, a cellulose-based compound capable of imparting viscosity can be further included. As the cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and their alkali metal salts can be mixed and used. The alkali metal can be Na, K, or Li.

[0131] The dry binder may be a polymer material capable of becoming fibers (eg, in the form of fibers), and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or (eg, any suitable) combinations thereof.

[0132] Conductive Materials

[0133] A conductive material (e.g., an electrical conductor) is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum silver, etc.; conductive polymers such as polyphenylene derivatives; or (e.g., any appropriate) mixture thereof

[0134] Based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0wt% to about 5wt% of the conductive material.

[0135] Negative electrode current collector

[0136] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm or about 7 μm to about 10 μm.

[0137] Electrolytes

[0138] An electrolyte for a rechargeable lithium battery may include a non-aqueous organic solvent and a lithium salt.

[0139] The non-aqueous organic solvent is used as a medium for transferring (e.g., transporting) ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, or (e.g., any appropriate) combinations thereof.

[0140] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In one or more embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond, etc.); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.

[0141] The non-aqueous organic solvent may be used alone or as a mixture of two or more types (or species), and if (for example, when) used as a mixture of two or more types (species), the mixing ratio may be suitably or appropriately adjusted according to the desired or suitable battery performance, which is widely applicable to those skilled in the art.

[0142] If (for example, when) a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.

[0143] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed and used in a volume ratio of about 1:1 to about 30:1.

[0144] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate or ethylene carbonate-based compounds to improve the battery cycle life.

[0145] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, and the like.

[0146] The lithium salt dissolved in the organic solvent supplies lithium ions in the battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are each independently an integer of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).

[0147] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If the concentration of the lithium salt is within the above range, the electrolyte may have suitable or appropriate ionic conductivity (e.g., have appropriate ionic conductivity) and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently moved.

[0148] Diaphragm

[0149] Depending on the type (or kind) of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0150] The separator may include a porous substrate and a coating on one or both surfaces (eg, opposite surfaces) of the porous substrate, the coating including an organic material, an inorganic material, or a combination thereof (eg, any suitable one).

[0151] The porous substrate may be a polymer film formed from any one polymer selected from the following and / or a copolymer or mixture of two or more thereof: polyolefins (such as polyethylene and / or polypropylene), polyesters (such as polyethylene terephthalate and / or polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon).

[0152] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0153] The organic material may include a (meth)acryl-based copolymer including: a first structural unit derived from (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof.

[0154] The inorganic material may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and (e.g., any suitable) combinations thereof, but the present disclosure is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0155] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.

[0156] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.

[0157] The embodiments and comparative examples of the present disclosure are described in more detail. However, the following embodiments are merely examples of the present disclosure, and the present disclosure is not limited to the following embodiments.

[0158] Example 1

[0159] 1. Preparation of positive electrode active material

[0160] Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1 and then subjected to a first heat treatment at 850 °C for 8 h in an oxygen atmosphere to prepare a LiNi 0.75 Mn 0.23 Al 0.02 O2 composition and an average particle size of about 14 μm (D 50 ) in the form of secondary particles of a lithium nickel manganese composite oxide.

[0161] After aluminum sulfate is mixed with distilled water as a solvent, lithium nickel manganese composite oxide is added thereto, and then mixed for 20 minutes to 60 minutes. In this article, based on 100mol% of the total metal other than lithium in the final positive electrode active material, the aluminum content (e.g., amount) in aluminum sulfate is designed to be 1.0mol%. Subsequently, cobalt sulfate is added thereto and then mixed for 10 minutes to 40 minutes. In this article, based on 100wt% of the total metal other than lithium in the final positive electrode active material, the manganese content (e.g., amount) in manganese sulfate is designed to be 0.2mol%. After removing the solvent from the mixed solution, the residue is dried at 190°C and subjected to a second heat treatment at 825°C for 8 hours under an oxygen atmosphere to prepare the final positive electrode active material.

[0162] 2. Preparation of rechargeable lithium battery cells

[0163] Based on the total weight of the positive electrode active material layer slurry, 98.5wt% of the prepared positive electrode active material, 1.0wt% of the polyvinylidene fluoride binder and 0.5wt% of the carbon nanotube conductive material were mixed to prepare the positive electrode active material layer slurry, and the slurry was coated on an aluminum foil positive electrode current collector, and then dried and pressed to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10mg / cm 2 , and the density of the positive electrode active material layer in the final pressed positive electrode was about 3.4 g / cc.

[0164] The negative electrode active material layer slurry was prepared by mixing 97.5 wt % of a graphite negative electrode active material, 1.5 wt % of carboxymethyl cellulose and 1 wt % of styrene butadiene rubber in water as a solvent based on the total weight of the negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil negative electrode current collector, and then dried and pressed to prepare a negative electrode.

[0165] Subsequently, a rechargeable lithium battery cell is prepared (for example, in a suitable method) using a polytetrafluoroethylene separator and an electrolyte solution prepared by mixing ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7 and dissolving 1M LiPF6 in the mixed solvent.

[0166] Comparative Example 1

[0167] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that LiNi 0.75 Mn 0.23 Al 0.02 A composite oxide of O2 itself is used as a positive electrode active material which is not coated with Al and not coated with Mn.

[0168] Comparative Example 2

[0169] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by dry coating only Al without coating Mn.

[0170] The Al dry coating method is carried out as follows. 0.75 Mn 0.23 Al 0.02 A lithium nickel manganese-based composite oxide of a composition of 200 Å to 1000 Å was mixed with an aluminum oxide powder, and then the mixture was heat-treated at 825° C. for 8 hours in an oxygen atmosphere to prepare a positive electrode active material dry-coated with Al.

[0171] Comparative Example 3

[0172] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by wet coating of Al without coating Mn.

[0173] For example, aluminum sulfate is mixed with distilled water as a solvent, and lithium nickel manganese composite oxide (LiNi 0.75 Mn 0.23 Al 0.02 O2), then mixing them for 20 to 60 minutes, removing the solvent therefrom, and drying the residue at 190° C. and subjecting it to a second heat treatment at 825° C. for 8 hours in an oxygen atmosphere to prepare a positive electrode active material of Comparative Example 3.

[0174] Comparative Example 4

[0175] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by wet coating only Mn without coating Al.

[0176] For example, by using lithium nickel manganese composite oxide (LiNi 0.75 Mn 0.23 Al 0.02 O2) was added to distilled water as a solvent, manganese sulfate was added thereto, and then they were mixed for 10 minutes to 40 minutes, the solvent was removed therefrom, and the residue was dried at 190°C and subjected to a second heat treatment at 825°C for 8 hours in an oxygen atmosphere to prepare a positive electrode active material of Comparative Example 4.

[0177] Evaluation Example 1: Analysis of Positive Electrode Active Material

[0178] After the positive electrode active material particles of Example 1 were cut using a focused ion beam (FIB), the cross section was subjected to SEM-EDS and HR-STEM analyses. Figure 5is a SEM-EDS analysis image of a cross section of the positive electrode active material of Example 1, in which Mn is highlighted, and Figure 6 Figure 2 is an image from the same analysis with Al highlighted.

[0179] refer to Figure 5 and Figure 6 A first coating layer containing a high density of Al is formed on the surface of the core particle with a substantially uniform thickness, and a second coating layer containing Mn is formed on the first coating layer.

[0180] Figure 7 HR-STEM image of a cross section of the positive electrode active material of Example 1, in which the first coating layer, the second coating layer and the core particle each have a layered structure.

[0181] Evaluation Example 2: Charge / discharge characteristics and high temperature cycle life characteristics

[0182] At 25° C., the rechargeable lithium battery cells according to Example 1 and Comparative Examples 1 to 4 were charged to 4.45 V at a constant current of 0.2 C and to 0.05 C at a constant voltage, and then discharged to a cut-off voltage of 3.0 V at 0.2 C as initial charge and discharge, wherein the initial discharge capacity (i.e., 4.45 V capacity) was measured.

[0183] Subsequently, at 45°C, the rechargeable lithium battery cell was charged at 1.0C and discharged at 1.0C in a voltage range of 3.0V to 4.45V, repeated 25 times or more, wherein the discharge capacity after the 25th cycle was measured to calculate the ratio of the discharge capacity after the 25th cycle to the initial discharge capacity (i.e., high temperature cycle life), and the results are shown in Table 1.

[0184] (Table 1)

[0185]

[0186] Referring to Table 1, the rechargeable lithium battery cell of Example 1 achieves high initial discharge capacity and high temperature cycle-life characteristics compared to the rechargeable lithium battery cells of Comparative Examples 1 to 4.

[0187] When describing embodiments of the present inventive concepts, the use of “may” refers to “one or more embodiments of the present inventive concepts”.

[0188] As used herein, the term "about" and similar terms are used as terms of approximation rather than as terms of degree, and are intended to account for the inherent deviations in measured or calculated values ​​that would be recognized by one of ordinary skill in the art. "About" as used herein includes the stated value and means within an acceptable range of deviations for the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations of the stated value, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0189] Furthermore, any numerical range set forth herein is intended to include all sub-ranges of the same numerical precision falling within the set forth range. For example, the range of "1.0-10.0" is intended to include between the set forth minimum value 1.0 and the set forth maximum value 10.0 (including 1.0 and 10.0), that is, all sub-ranges (such as, for example, 2.4-7.6) having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0. Any maximum numerical limit set forth herein is intended to include all lower numerical limits falling therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits falling therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-range falling within the range explicitly set forth herein.

[0190] Unless otherwise defined, in the present disclosure, if (for example, when) the particles are spherical, the term "particle size" refers to the average diameter, and if (for example, when) the particles are non-spherical, the term "particle size" refers to the average major axis length.

[0191] The battery management system (BMS) device and / or any other related device or component according to the embodiments of the present invention described herein may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. Further, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. Further, the various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device (such as, for example, a random access memory (RAM)). The computer program instructions may also be stored in other non-temporary computer-readable media (such as, for example, a CD-ROM, a flash drive, etc.). Moreover, those skilled in the art should recognize that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a particular computing device may be distributed on one or more other computing devices.

[0192] While the disclosure has been described in connection with what are presently considered to be practical example embodiments, it should be understood that the disclosure is not limited to the disclosed embodiments, but on the contrary, the disclosure is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.

Claims

1. A positive electrode active material comprising: The core particle includes a layered lithium nickel manganese composite oxide, a first coating layer, on the surface of the core particle and comprising Al, and A second coating layer is on the first coating layer and includes Mn.

2. The positive electrode active material according to claim 1, wherein the layered lithium nickel manganese composite oxide comprises: 60 mol% to 80 mol% nickel, and greater than or equal to 10 mol % of manganese, Each of 60 mol % to 80 mol % of nickel and 10 mol % or more of manganese is based on 100 mol % of the total amount of metals other than lithium in the layered lithium nickel manganese-based composite oxide.

3. The positive electrode active material according to claim 1, wherein the layered lithium nickel manganese-based composite oxide further comprises greater than 0 mol% and less than or equal to 3 mol% of aluminum based on 100 mol% of the total amount of metals other than lithium in the layered lithium nickel manganese-based composite oxide.

4. The positive electrode active material according to claim 1, wherein the layered lithium nickel manganese based composite oxide includes at most 0.01 mol% of cobalt based on 100 mol% of the total amount of metals other than lithium in the layered lithium nickel manganese based composite oxide.

5. The positive electrode active material according to claim 1, wherein the layered lithium nickel manganese composite oxide is represented by Chemical Formula 1: [Chemical formula 1] Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 Wherein in Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from boron, barium, calcium, cerium, chromium, iron, magnesium, molybdenum, niobium, silicon, tin, strontium, titanium, vanadium, tungsten, yttrium and zirconium, and X is one or more elements selected from fluorine, phosphorus and sulfur. 6 . The positive electrode active material of claim 1 , wherein the first coating layer and the second coating layer are each independently in the form of a continuous film.

7. The positive electrode active material according to claim 1, wherein The thickness of the first coating is 5nm to 40nm, and The thickness of the second coating layer is less than or equal to 10 nm. 8 . The positive electrode active material of claim 1 , wherein a ratio of a thickness of the second coating layer to a thickness of the first coating layer is less than or equal to 0.

5.

9. The positive electrode active material according to claim 1, wherein The amount of Al from the first coating layer is 0.1 mol% to 2 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, and The amount of Mn from the second coating layer is 0.01 mol% to 1 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material.

10. The positive electrode active material according to claim 1, wherein The amount of Al from the first coating layer is 0.5 mol% to 1.5 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, and The amount of Mn from the second coating layer is 0.05 mol% to 0.5 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material. 11 . The positive electrode active material of claim 1 , wherein a ratio of an amount of Mn from the second coating layer to an amount of Al from the first coating layer is less than 0.

5.

12. The positive electrode active material according to claim 1, wherein The first coating comprises aluminum oxide, lithium aluminum oxide, or a combination thereof, and The second coating layer includes manganese oxide, lithium manganese oxide, aluminum manganese oxide, lithium aluminum manganese oxide, or a combination thereof. 13 . The positive electrode active material of claim 1 , wherein the first coating layer and the second coating layer each independently have a layered structure. 14 . The positive electrode active material of claim 13 , wherein the second coating layer further has a spinel structure.

15. The positive electrode active material according to claim 1, wherein The core particle is in the form of a secondary particle made by aggregating a plurality of primary particles, and The positive electrode active material further includes a grain boundary coating portion including Al and on a surface of the primary particle of the secondary particle. 16 . The positive electrode active material according to claim 15 , wherein the amount of Al from the grain boundary coating portion is less than the amount of Al from the first coating layer based on 100 mol % of total metals other than lithium in the positive electrode active material.

17. The positive electrode active material according to claim 1, wherein the average particle size D of the positive electrode active material is 50 It is 10μm~20μm.

18. A method for preparing a positive electrode active material, the method comprising: A nickel-manganese-based composite hydroxide and a lithium raw material are mixed and subjected to a first heat treatment to obtain a layered lithium-nickel-manganese-based composite oxide, mixing an Al raw material with an aqueous solvent, adding the layered lithium nickel manganese-based composite oxide and mixing to prepare a first mixture, mixing a Mn raw material with the first mixture to prepare a second mixture, and The second mixture is dried and subjected to a second heat treatment.

19. The method according to claim 18, wherein the layered lithium nickel manganese composite oxide comprises: 60 mol% to 80 mol% nickel, greater than or equal to 10 mol % of manganese, 0 mol% to 3 mol% aluminum, and 0 mol% to 0.01 mol% of cobalt, Each of 60 mol% to 80 mol% nickel, 60 mol% to 80 mol% nickel, 0 mol% to 3 mol% aluminum and 0 mol% to 0.01 mol% cobalt is based on 100 mol% of the total amount of metals other than lithium in the layered lithium nickel manganese-based composite oxide.

20. The method of claim 18, wherein The amount of Al from the Al raw material is 0.1 mol% to 2 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, and The amount of Mn from the Mn raw material is 0.01 mol% to 1 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material.

21. The method of claim 18, wherein The Al raw material includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof, and The Mn raw material includes manganese nitrate, manganese sulfate, manganese carbonate, manganese hydroxide or a combination thereof.

22. The method of claim 18, wherein a solution obtained by mixing the Al raw material in the aqueous solvent has a pH of 1.5 to 3.

5.

23. The method of claim 18, wherein The first heat treatment is performed at 750°C to 950°C, and The second heat treatment is performed at 700°C to 850°C.

24. A positive electrode comprising: a positive electrode current collector, and A positive electrode active material layer, on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 17 or a positive electrode active material prepared by the method according to any one of claims 18 to 23.

25. The positive electrode of claim 24, wherein the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 . 26 . The positive electrode according to claim 24 , wherein the positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.

27. A rechargeable lithium battery comprising: The positive electrode according to claim 24, negative electrode, and Electrolytes.

28. The rechargeable lithium battery of claim 27, wherein a charging voltage of the rechargeable lithium battery is greater than or equal to 4.45V.